HUBUNGAN ANTARA KEPUASAN SISWA DAN PERSEPSI KINERJA GURU PROFESIONAL DENGAN HASIL BELAJAR SISWA PADA MATA PELAJARAN PEKERJAAN DASAR ELEKTROMEKANIK - Siti Mardiah; Soeprijanto; Farried Wadjdi (Journal of Electrical Vocational Education and Technology, 2017)
This research aims to determine the relationship between student satisfaction and perception of professional teacher performance with student learning outcomes electromechanical basic work subjects. This research was conducted in 5 Vocational High School of Jakarta. The method used is the method of survey. Collecting data using techniques of observation and questionnaires. Affordable population in this study were students of the X grade electrical engineering student totaling 90 students and the sample research taken as many as 40 students. The test results by using a correlation coefficient of pearson product moment obtained value rxy X1 0.920 rxy X2 0,940 dan R 0,722. This means that together there is a positive relationship between student satisfaction about professional teacher performance with student learning outcomes electromechanical basic work subjects. From t-test calculations obtained X1 tcount > ttable (14,52 > 2,02), which showed a significant relation between the variable X1 is student satisfaction about professional teacher performance with variable Y is Student Learning Outcomes Electromechanical basic work Subject and for variable X2 obtained tcount > ttable (17,05 > 2,02), which showed a significant relation between the variable X1 is professional teacher performance with variable Y is Student Learning Outcomes Electromechanical basic work Subject. From the calculation result obtained coefficient of determination X1 37.25% so that it can be said that the variable Y Student Learning Outcomes Electromechanical basic work Subject determined by variable X1 student satisfaction about professional teacher performance by 84,73% And coefficient of determination X2 88,44% so that it can be said that the variable Y Student Learning Outcomes Electromechanical basic work Subject determined by variable X2 professional teacher performance by 88,44%. To improve students' satisfaction in the future, it is expected that teachers can use more appropriate and suitable learning method with the students and to improve teacher performance expected school always monitor teacher performance every year. Abstrak Penelitian ini bertujuan untuk mengetahui hubungan antara kepuasan siswa dan persepsi kinerja guru profesional dengan hasil belajar siswa mata pelajaran pekerjaan dasar elektromekanik. Penelitian ini dilakukan di SMK N 5 Jakarta. Metode yang digunakan adalah metode survei. Pengumpulan data menggunakan teknik pengamatan dan kuesioner. Populasi dalam penelitian ini adalah siswa kelas X TIPTL yang berjumlah 90 siswa dan sampel penelitian diambil sejumlah 40 siswa dengan cara stratified random sampling. Data yang telah terkumpul akan dioleh dengan uji hipotesis setelah data memenuhi persyaratan normalitas, keberartian dan linieritas. Hasil penelitian menggunakan uji koefisien korelasi dengan menggunakan product moment dari Pearson diperoleh nilai rxy X1 0,920, rxy X2 0,940 dan R 0,722. Hal ini berarti secara bersama-sama terdapat hubungan yang positif antara kepuasan siswa tentang kinerja guru profesional dan kinerja guru profesional dengan hasil belajar siswa pekerjaan dasar elektromekanik. Dari perhitungan uji-t didapat X1 thitung > ttabel (14,52 > 2,02), yang menunjukkan adanya hubungan yang signifikan antara variabel X1 yaitu kepuasan siswa tentang kinerja guru profesional dengan variabel Y yaitu hasil belajar pekerjaan dasar elektromekanik dan untuk X2 didapat thitung > ttabel (17,05 > 2,02), yang menunjukkan adanya hubungan yang signifikan antara variabel X2 yaitu kinerja guru profesional dengan variabel Y yaitu hasil belajar pekerjaan dasar elektromekanik. Dari hasil perhitungan diperoleh koefisien determinasi X1 84,73%, sehingga dapat dikatakan bahwa variabel Y hasil belajar pekerjaan dasar elektromekanik ditentukan oleh variabel X1 kepuasan siswa tentang kinerja guru profesional sebesar 84,73% dan koefisien determinasi X2 88,44%, sehingga dapat dikatakan bahwa variabel Y hasil belajar pekerjaan dasar elektromekanik ditentukan oleh variabel X2 kinerja guru profesional sebesar 88,44%.